CRITICAL INTERPRETATION OF WEALTHINESS AND WICKEDNESS IN CHARLES DICKENS' GREAT EXPECTATIONS - ABODOHOUI, Alexis (My University, 2023)
This paper about the question of human living standard and a community welfare plays a prominent role in people’s daily life. From this perspectives, this study focuses on wealthiness and wickedness with a special reference to Charles Dickens’ Great Expectations, a Victorian period writer. It is simply significant because it aims at indicating ways and means people can manage the implications of wealthiness and wickedness. To achieve my goal and the topic dealing with people’s state of being and their relationship with their fellows, I have used psychoanalysis and New Historicism as literary theories to critically appreciate how wealthiness can lead to wickedness. My analysis has revealed that Charles Dickens resorts to his fictional work as a strategy to depict the concepts of wealthiness and wickedness. He also pinpoints wealthiness as an obstacle for fulfilment, social development and well-being in his era.
Keywords: Victorian era; wealthiness; wickedness; people; New Historicism